ANALISIS PENGUKURAN KINERJA DENGAN MENGGUNAKAN KONSEP VALUE FOR MONEY PADA PEMERINTAH KOTA LHOKSEUMAWE: (STUDI KASUS PADA DPKAD KOTA LHOKSEUMAWE PERIODE 2014-2016) - Indrayani, Indrayani; Khairunnisa, Khairunnisa (Department of Accounting, Faculty of Economics & Business, 2018)
This study aimed to determine the performanceÂ of the Office of Revenue Finance and Regional Assets (DPKAD) Lhokseumawe City by using the concept of Value For Money. This research was conducted by taking data for 3 years, from 2014 to 2016. This research used secondary data. The method of data analysis used is descriptive qualitative analysis method. Based on the researchÂ result by using Value For Money concept based on 3 main elements such as economic, efficiency and effectiveness show that: Economic ratio, get 86,54%, 82,64% and 71,43% which means the economic ratio was under 100% during 2014-2016 and the result of this ratio indicated that the economic ratio criterion obtained the â€œeconomicalâ€ category.the efficiency ratios during the research year of this ratio were 94,69%, 105,17% and 97,95%, although in 2015 the ratio was less efficient because it was in percentage above 100%. However, the overall performance of the Lhokseumawe City Government has been categorized as â€œefficientâ€. While the effectiveness ratio, obtained 96,53%, 86,65% and 76,98%, where the percentage ratio below 100% indicates that this ratio obtains â€œineffectiveâ€ criterion. Based on the result, the concept of Value For Money is very good to be applied on DPKAD of Lhokseumawe city because it can provide a more structured and comprehensive performance overview.